Down to the bone: the role of overlooked endolithic microbiomes in reef coral health - Pernice, Mathieu (ISME J, 2019)
Reef-building corals harbour an astonishing diversity of microorganisms, including endosymbiotic microalgae, bacteria, archaea, and fungi. The metabolic interactions within this symbiotic consortium are fundamental to the ecological success of corals and the unique productivity of coral reef ecosystems. Over the last two decades, scientific efforts have been primarily channelled into dissecting the symbioses occurring in coral tissues. Although easily accessible, this compartment is only 2–3 mm thick, whereas the underlying calcium carbonate skeleton occupies the vast internal volume of corals. Far from being devoid of life, the skeleton harbours a wide array of algae, endolithic fungi, heterotrophic bacteria, and other boring eukaryotes, often forming distinct bands visible to the bare eye. Some of the critical functions of these endolithic microorganisms in coral health, such as nutrient cycling and metabolite transfer, which could enable the survival of corals during thermal stress, have long been demonstrated. In addition, some of these microorganisms can dissolve calcium carbonate, weakening the coral skeleton and therefore may play a major role in reef erosion. Yet, experimental data are wanting due to methodological limitations. Recent technological and conceptual advances now allow us to tease apart the complex physical, ecological, and chemical interactions at the heart of coral endolithic microbial communities. These new capabilities have resulted in an excellent body of research and provide an exciting outlook to further address the functional microbial ecology of the “overlooked” coral skeleton.